Deracemization of α-Substituted Carbonyl Compounds via Catalytic Enantioselective Protonation of their Corresponding Enolates - Claraz, Aurelie; Oudeyer, Sylvain; Levacher, Vincent (Current Organic Chemistry, 2012)
Enantioselective protonation of prostereogenic enol derivatives has been shown to be an attractive route for the preparation of enantiomerically pure carbonyl compounds. Indeed, this strategy can be regarded as a two steps deracemization process starting from racemic carbonyl compounds. It has therefore attracted a lot of research efforts in the last twenty years to design general and efficient catalytic approaches. Herein, we report an up-to-date review of what have been done in the field from the pionner work to the latest developments. This manuscript is divided into three parts corresponding to the three main classes of enolates encountered in the enantioselective protonation namely lithium or silyl enolates and enol acetates. For each type of substrates, several approaches will be disclosed covering all the modern chemical tools (including organometallic, organocatalytic or enzymatic processes) recently developed.
Keywords: ammonium fluoride